Biological Activity of Tannins from Acacia mangium Bark Extracted by Different Solvents - E Wina; Susana I W.R; B Tangendjaja (Media Peternakan, 2010)
Acacia mangium bark is abundant byproduct of wood industry in Indonesia. It is underutilized and mainly used as fire wood for the wood industry. The bark contains high level of tannin but the tannin has not been extracted or produced commercially. Tannin isolate can be used for several purposes such as tanning agent for leather, adhesive for plywood or particle board, etc. In ruminant, tannin can be detrimental but can also be beneficial. This experiment was aimed of getting the highest yield of tannin extract with the highest biological activity in rumen fermentation. Nine different solvents at different temperatures were used to extract tannin from A. mangium bark. The extracts were analyzed for their tannin contents and biological activities. Tannin content was analyzed using folin ciocalteau and butanol-HCl methods. Biological activity was described as a percentage of an increase in gas production in the in vitro rumen-buffer fermentation, with and without addition of PEG. The results show that Na2SO3 solution extracted more tannin than other solutions and the higher the concentration of Na2SO3 solution, the higher the yield of tannin extract. The solution of 6% sodium sulphite gave the highest yield of tannin extract (31.2% of original bark sample) and the highest concentration of tannin (18.26%) but produced a negative effect on in vitro fermentation (% increase of gas production = 2.70%). Extraction with 50% acetone gave a high yield of extract (22.28% of original bark) which contained 12.98% of tannin and showed the highest biological response (% increase of gas production = 216%). In conclusion, sodium sulphite solution is not recommended for tannin extraction if the tannin will be used as feed additive in ruminant feed; on the other hand, the aqueous acetone (50% acetone) solution is a better choice to be used.